Deconstruir el amor a partir de El príncipe y la modista (2018) de Jen Wang - Abellán Hernández, Maria (CEM – Cultura, Espaço & Memória, 2020)
This paper deals with constructions of the romantic love ideal as narrative formulae inscribed in cultural products, focusing on «comic» as a médium hardly attended in Visual Studies. We look this narrative’s doublé nature as a union of the content (story) and the traditional form (discourse) in the discipline of audiovisual narrative. In this direction, we will review some of the critical texts dealing with both the romantic ideal of which consumers participate as well as the use of visual images employed in this stories, as a way of tentatively posing a narrative canon. Through the critical analysis of The Prince and The Dressmaker (2018) by Jen Wang, we will explore the subversive strategies of the romantic canon in order to, ultimately, concretize these aspects in a podagogical model concerned with new roles and construction mechanisms of romantic love and gender roles in this type of story. This analysis will show, beside his loyalty to classic amorous schemes, Wang’s innovations in the representation of characters and their narrative roles.